1987
DOI: 10.1038/ki.1987.68
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intraperitoneal calcitriol on calcium and parathyroid hormone

Abstract: Parathyroid suppression by intraperitoneal calcitriol (1,25(OH)2D3) during peritoneal dialysis. The purpose of this study was to determine if parathyroid hormone (PTH) suppression could be achieved by increasing calcium mass transfer (Ca MT) with high dialysate Ca (4 mEq/liter) or via intraperitoneal (i.p.) 1,25(OH)2D3 in patients undergoing continuous ambulatory peritoneal dialysis. Eleven patients were dialyzed for two months with standard Ca dialysate (3.5 mEq/liter) followed by two months with 4.0 mEq/lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Plasma levels of 1,25(OH)2D were measured by the method of Reinhardt et al (18). The characterization ofthe assay by our laboratory has been published elsewhere (19). All samples from each patient were determined in sextuplicate in the same assay.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma levels of 1,25(OH)2D were measured by the method of Reinhardt et al (18). The characterization ofthe assay by our laboratory has been published elsewhere (19). All samples from each patient were determined in sextuplicate in the same assay.…”
Section: Methodsmentioning
confidence: 99%
“…Calderaro et al [22] noted a negative balance of 50 ± 9 mg/day using a dialysate calcium of 3 mEq/1. We [23] found that patients not taking calcium supplements with ionized calcium levels of 4.72 ± 0.09 mg/dl had a net uptake of 37 ± 17 mg/day with the standard 3.5 mEq/1 calcium dialy sate. The net uptake more than doubled to 84 ± 6 mg/day with the use of a dialysate solution containing 4.0 mEq/1 of calcium.…”
Section: Calciummentioning
confidence: 93%
“…This finding suggested that intravenous l,25(OH)2-vitamin D may directly suppress PTH secretion. Recent studies employing calcium infusions suggest that the mechanism may, in part, be due to increased sensitivity of the gland to ambient calcium levels [45], We, therefore, sought to determine if PTH suppression could be achieved by either increasing calcium mass transfer with a high dialysate calcium (4 mEq/1) or intraperitoneal 1,25(OH)2-vitamin D in patients undergoing CAPD [23], Eleven patients were dialyzed for 2 months with standard calcium dialysate (3.5 mEq/1), followed by 2 months with 4.0 mEq/1 cal cium dialysate and then 3 months with noc turnal dwells containing intraperitoneal l,25(OH)2-vitamin D. Ionized calcium and total calcium did not change with the higher dialysate calcium. However, both rose signif icantly with the use of intraperitoneal 1,25(OH)2-vitamin D. Phosphorus levels did not change.…”
Section: Parathyroid Hormonementioning
confidence: 99%
“…For example, desferrioxamine increased dialysate aluminum 4-fold in an intoxicated patient, reducing plasma levels of aluminum [59]. As another example of drug therapy during CAPD, intra peritoneal absorption of 1,25-dihydroxyvitamin D3 can raise serum calcium and can depress serum PTH more effectively than increasing dialysis fluid calcium does [60].…”
Section: Calcium and Phosphorus And Bone Metabolismmentioning
confidence: 99%